QUIZLET APPLICATION EFFECT ON SENIOR HIGH SCHOOL STUDENTS VOCABULARY ACQUISITION - M Rizky Setiawan; Nurhidayanto Pancoro Setyo Putro (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
Vocabulary is one of the language features that should be acquired by the students to support them learning other language skills. The students will be easier to receive or produce the English language if they remember the considerable words. After being observed in the actual classroom, however, most students seem difficult to acquire words. Moreover, the influence of using media such as Quizlet Application on vocabulary acquisition needed to be proved by involving large participants since that application was not widely used by EFL teachers in Indonesian educational context. The study aims to find out if there is any significant difference in the grade ten students’ vocabulary acquisition between those who use Quizlet Application (QA) and those who do not use it in learning vocabulary. The participants were 110 tenth-grade students in senior high school. Their vocabulary knowledge was assessed through pre-test and post-test conducted before and after the treatment was given. The research finding reveals that there was a significant difference in students’ vocabulary acquisition between those who used Quizlet Application and those who were taught using the conventional method in learning vocabulary. That finding was indicated by the value of significant which was below 0.05. Moreover, it is also found that QA was less effective on students’ vocabulary acquisition while the conventional method was not effective to students in obtaining words.